Coping Strategies and Complicated Grief in a Substance Use Disorder Sample - Caparrós, Beatriz; Masferrer, Laura (Frontiers in Psychology, 2021)
Background: Previous research has identified a link between the loss of a significant person, grief complications and substance abuse. People with substance use disorder (SUD) are more vulnerable to complicated grieving symptoms following loss. From sociocognitive theories the model of coping with stress assumes that substance use is one of the responses used to cope with traumatic life events. The main objective of this study is to identify the coping strategies of people with substance use disorder (SUD) and to analyse their relationship to complicated grief. Methods: A sample of 196 bereaved drug-dependent patients was assessed, after providing written consent, in sociodemographic variables, drug and bereavement related characteristics, complicated grief symptomatology (Inventory of Complicated Grief) and coping strategies (Coping Strategies Inventory). Results: there are differences in relation to the coping strategies used among patients with complicated grief, using more those focused on emotional expression, social withdrawal, wishful thinking and self-criticism. Conclusions: We can conclude that, in general, complicated grief in patients with SUD is more associated with the use of less adaptive coping strategies. This data can contribute to a better understanding of the different variables involved in the grieving process among people with Substance Use Disorder. It is important to point out the clinical implications of addressing what the coping strategies associated with improved grief outcomes among people with addiction problems are.